PENERAPAN KEBIJAKAN PENJADWALAN ULANG PADA RUANG LINGKUP SINGLE MACHINE UNTUK MEMINIMASI TOTAL TARDINESS (Studi Kasus di PT. Indonesia Steel Tube Works) - Denny Nurkertamanda; Zaenal Fanani; Anna Kusuma Wardhani (TEKNIK, 2009)
Customer satisfaction is the most important thing to be considered to keep the customer trust of a productor even of a company. Giving the satisfaction to the customer can be achieved by several ways and on timedelivery product is one of them. It is true that some problems can often occur during that achievement andmay hinder the on time delivery fulfillment. One of the major elements that hold the key role of on timedelivery fulfillment is production scheduling. The implementation of appropriate production schedulingpolicy will determine the accomplishment of on time delivery fulfillment in some ways. This statement isalso works for Indonesia Steel Tube Works Ltd., as a company that always cares about the customersatisfaction on quality and on time delivery. If we observe the production scheduling records of IndonesiaSteel Tube Works Ltd. we can find some lateness problems that in some case happened in an extensiveinterval of tardiness. The company only runs the production scheduling based on the group of pipediameter. This policy seems cannot well handle the rush orders that often emerge on every schedulingperiod and effect in tardiness problems. The company needs to consider the rescheduling policy with theaim of reducing the tardiness that often emerges because of the rush order disruption.